PENGARUH DEBT TO EQUITY RATIO DAN RETURN ON ASSETS TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ayu Puspitaningtyas (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
This study aims to determine the effect of debt to equity ratio and return on assets of stock price on food and beverages sector in Indonesia Stock Exchange. This study used secondary data, with samples 9 food & beverages companies in Indonesia Stock Exchange during the study period 2016-2018. Independent variables in this study are debt to equity ratio and return on assets. This study used purposive sampling technique. The method of data analysis used multiple regression analysis. Based on results of the study, only debt to equity ratio have no significant effect on stock price. Meanwhile, the F test result shows that Debt to Equity Ratio and Return on Assets jointly have effect on stock price.